Concentration of xylooligosaccharides with a low degree of polymerization using membranes and their effect on bacterial fermentation. (19th September 2020) - Singh, Ramkrishna D.; Muir, Jane; Arora, Amit
Abstract: Xylooligosaccharide (XOS) liquor, enzymatically obtained from almond‐shell hemicellulose and consisting primarily of xylobiose and xylotriose, was refined and concentrated using a combination of membranes and ion‐exchange resin. The concentrated liquor was used for an in vitro fermentation study utilizing different strains of Lactobacillus and Bifidobacterium . Upon ultrafiltration with a 10 kDa membrane, high molecular‐weight components, including enzymes and color‐imparting impurities, could be removed from the liquor. Upon nanofiltration with a 150 Da membrane, at a volume:concentration ratio of 8.9, a retentate containing 79% xylobiose and 41.3% xylotriose was obtained. At the end of filtration, 69.6 ± 3.8% of the initial XOS was recovered, with concentrated xylobiose and xylotriose in the retentate. The resin treatment further improved the purity of the XOS concentrate via decoloration and deacidification. Among the evaluated strains of Lactobacillus and Bifidobacterium, L. acidophilus, B. adolescentis, and B. brevis could ferment XOS to a varying extent, as indicated by their difference in growth, to produce acetate as a predominant short‐chain fatty acid. For Lactobacillus, a 10–12‐fold increase in the bacterial population was observed at the end of 48 h. On the other hand, Bifidobacterium grew slowly to show about a 1.2 to fourfold increase in the bacterial population at the end of 72 h. A bacterial preference for fermenting xylobiose rather than xylotriose or xylotetrose was also observed, justifying the production of XOS with a low degree of polymerization. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd